Evaluating the potential biological control of Margarodes prieskaensis using South African entomopathogenic fungi, and/or entomopathogenic nematodes - Erasmus, Talitha (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConsEcol)--Stellenbosch University, 2023.